Effect of local administration of doxycycline on bone regeneration/formation: A systematic review - Tatiane Cristina Dotta; Michelle Chang; Hian Parize; Fellipe Augusto Tocchini de Figueiredo; Hugo Gaêta-Araujo; Dalva Cruz Laganá; Johannes Kleinheinz; Vinicius Pedrazzi (Elsevier, 2024)
Objective: To evaluate the effects of local administration of doxycycline on bone regeneration and formation. Design: An electronic search was conducted in the PubMed, EMBASE, Scopus, Web of Science, and Cochrane Library databases from November 2023 to July 2024. Human and animals' studies that assessed the local effect of doxycycline on bone formation and regeneration using histological and histomorphometric measures were included. The risk of bias was evaluated using the Joanna Briggs Institute (JBI) Critical Appraisal Tool for quasiexperimental studies. This review was registered in the PROSPERO database (CRD42024516306). Results: Of the 23 studies selected for full-text analysis, five were deemed eligible for this review. No human clinical trials were found. The studies included evaluations of 94 rats, 28 rabbits, and 6 dogs. The histological and histomorphometric methods used varied among the studies. Limitations of the evidence included the heterogeneity of the analyses and the methodologies of the included studies. Conclusions: The findings suggest that doxycycline may promote local bone formation and repair, and that its combination with other substances may enhance these effects in animal models. However, further translational research is required to confirm these results accurately and extend their applicability to human clinical studies.